Kajian Pembuatan Bioetanol dari Limbah Kulit Nanas (Ananas comosus. L) - Kurniati, Yuni; Khasanah, Iis Elfy; Firdaus, Kurniawati (Jurnal Teknik Kimia USU, 2021)
Ethanol is a fuel with a high octane number and is environmentally friendly. Bioethanol which can be made from biomass materials such as pineapple peel, is considered not to interfere with food security. With a fairly high carbohydrate and glucose content, pineapple can be converted into reducing sugars that can be fermented to produce ethanol. This study was conducted using the journal review method and aims to determine the mechanism, the variables that play the role, and the optimum conditions of fermentation in the manufacture of bioethanol from pineapple peel. The focus of the analysis was on hydrolysis, namely the type, concentration of the hydrolyzing agent, pH, temperature, and concentration of yeast in fermentation. The analysis from previous studies, the best hydrolysis was obtained by enzymatic hydrolysis using cellulase enzymes with a concentration of 1%-2%. The optimum pH of fermentation was found at pH 5 to pH 6, the fermentation temperature was 30 oC with a Saccharomyces cerevisiae concentration of 1.5% – 2%, and the optimum fermentation time occurred in the range of 48 to 96 hours. The high amount of reducing sugar produces a high amount of ethanol as well.